Neighborhood racial/ethnic segregation and cognitive decline in older adults. (September 2021) - Meyer, Oanh L.; Besser, Lilah; Mitsova, Diana; Booker, Michaela; Luu, Elaine; Tobias, Michele; Farias, Sarah Tomaszewski; Mungas, Dan; DeCarli, Charles; Whitmer, Rachel A.
Abstract: Social determinants of health, including neighborhood factors, play a key role in the health of diverse older adults. However, few longitudinal studies have examined the role of neighborhood racial/ethnic segregation on cognitive decline in diverse samples. We examined older non-Hispanic White (NHW), Black, and Latino participants evaluated at an Alzheimer's Disease Research Center. Neighborhood racial/ethnic segregation was measured using the Getis-Ord Gi * statistic, a spatial measure of clustering that was created for Latino and Black clustering separately. Cognitive outcomes included episodic memory, semantic memory, and executive function. We used mixed effects multivariable regression models to evaluate associations between segregation and cognitive function and decline. We had 452 individuals: 46% NHW, 26% Black, and 21% Latino in 309 census tracts with an average of 5.2 years of follow-up data (range 0.6–15.0). In analyses that adjusted for a variety of covariates (including neighborhood SES), individuals in neighborhoods with a higher clustering of Latino residents (higher Gi* statistic) had slower declines over time on semantic memory and those in neighborhoods with a higher clustering of Black residents had slower declines over time on episodic memory. In race/ethnicity-stratified adjusted analyses: for Black participants, the association between clustering and cognition was present for episodic memory and executive function, showing lower baseline scores in highly clustered Black and Latino neighborhoods, respectively. There was no association with cognitive change. Among Latino participants, highly clustered Latino neighborhoods were associated with lower baseline scores in semantic memory, but slower declines in episodic memory; Latinos living in neighborhoods with a greater clustering of Black residents also had slower declines in episodic memory. Among NHWs, residing in neighborhoods with a higher clustering of Latino residents was associated with slower declines over time on semantic memory. Segregated neighborhoods may be differentially associated with cognitive outcomes depending on individual race/ethnicity. Highlights: Social determinants of health affect cognition in ethnically diverse older adults. Residential segregation is a manifestation of historical racism. Segregation is complexly related to cognition at baseline and cognitive decline. More research is needed on complex associations of segregation with cognition.